Interculturality as a source of organisational positivity in expatriate work teams: An exploratory study. (25th December 2018) - Bachkirov, Alexandre Anatolievich
Abstract: This study explored the issues related to interculturality and organisational positivity in culturally diverse teams (CDTs). The findings showed that interculturality in the expatriate settings of the Arabian Gulf is linked to organisational positivity, the manifestations of which include enjoyment, relationship building through concerted efforts to learn about others, and family‐like work environments. Interculturality‐driven organisational positivity is posited to encourage humanistic management, the attributes of which are sensitivity to human suffering, open‐mindedness, fairness, and respect. Organisational positivity is also theorised to improve CDT performance and stimulate professional and personal learning. Theoretical and practical implications of the findings are discussed.